Compliance Model For Completeness Of Filling In Medical Records By Professional Care Providers (PPA) With Motivation As An Intervening Variable - Ratih Ariyanti Pratika; Duta Liana; Muhammad Fachruddin Arrozi (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Hospitals establish Minimum Service Standards (SPM) for medical records, specifically emphasizing the requirement for completeness in filling out medical records within 24 hours of service completion and achieving a 100% completeness standard for informed consent after receiving clear information. This study aims to develop a compliance model for Professional Care Providers (PPA) in filling out medical records, incorporating motivation as an intervening variable based on knowledge and attitude variables among inpatients at Cilincing Hospital. The sampling method employed is saturated sampling, with a total sample size of approximately 82 respondents. Path Analysis is utilized for data analysis, employing AMOS software. The research findings indicate a significant influence of knowledge, attitudes, and motivation of Professional Care Providers (PPA) on the overall compliance with the completeness of medical record filling, both collectively and individually. Moreover, the study reveals a significant impact of knowledge and attitudes on the motivation of Professional Caregivers (PPA). Additionally, motivation, acting as an intervening variable, demonstrates its ability to mediate the influence of knowledge and attitudes of Professional Care Providers (PPA) on compliance with the completeness of medical record filling.